2015
DOI: 10.1007/s00415-015-7948-4
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cortex and pulvinar abnormalities on diffusion-weighted imaging in status epilepticus

Abstract: The aim of this study was to analyze the pattern of magnetic resonance diffusion-weighted imaging (DWI) findings in status epilepticus in terms of clinical characteristics. Participants comprised 106 patients with status epilepticus who were admitted to our hospital and underwent DWI. Forty-five patients (42.5 %) showed abnormal findings on DWI and were divided into two groups, comprising 26 patients (24.5 %) with cortex lesions alone and 19 patients (17.9 %) with cortex and pulvinar lesions in the same hemisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
4
12
0
Order By: Relevance
“…Because these MRI changes are supposedly caused by continuous or repetitive epileptic activity, a higher proportion of patients with PMAs can be | 125 expected if MRI is performed during the SE instead of after its cessation. 24,28 Nevertheless, it is still possible to find these alterations for some time after the end of SE; the duration could depend on two factors: patient characteristics (eg, age, comorbidities), or seizure characteristics (type and duration of ictal activity).…”
Section: Discussionmentioning
confidence: 99%
“…Because these MRI changes are supposedly caused by continuous or repetitive epileptic activity, a higher proportion of patients with PMAs can be | 125 expected if MRI is performed during the SE instead of after its cessation. 24,28 Nevertheless, it is still possible to find these alterations for some time after the end of SE; the duration could depend on two factors: patient characteristics (eg, age, comorbidities), or seizure characteristics (type and duration of ictal activity).…”
Section: Discussionmentioning
confidence: 99%
“…Nakae et al presented 106 patients with DWI signal abnormalities in 42.5% of them; 24.5% presented with cortex lesions alone and 17.9% with both cortex and pulvinar ipsilateral lesions. They found that a long duration of SE (120 min) tended to be more prevalent in the group of both pulvinar and cortex lesions (57.9%), a trend that favors a spreading pattern of seizure discharge via cortico-pulvinar connections [16].…”
Section: Periictal Changes and Their Relation With Epileptogenic Networkmentioning
confidence: 97%
“…In some cases, the high DWI signal is accompanied by high signal in ADC map and corresponding hyperintensities in T2‐weighted and fluid‐attenuated inversion recovery (FLAIR) sequences representing vasogenic instead of cytotoxic edema . Of interest, especially in focal seizures, coherent and reproducible patterns of MRI alteration can be found in the areas of the highest seizure activity (eg, neocortex or mesolimbic structures) as well as in remote areas (eg, the homolateral pulvinar nucleus of the thalamus, the contralateral cerebellum, the basal ganglia, and the claustrum) showing that during SE sustained ictal activities involve complex cortico‐subcortical networks …”
Section: A Physiopathologic Framework For Periictal Imaging Abnormalimentioning
confidence: 99%